Advancements in Medical Physics: The Role of Quantum Computing in Enhancing Radiation Therapy Planning and Treatment Accuracy - Abdullah, Doha Jumaa Kamel; alhusaeen, Noor Alhuda Monadhel abd; Baqer, Amna Monaf Sadiq; younis, Ruqaya Husein Dlehm; Mohammed, Karar Mohammed Ali Jassim (American Journal of Botany and Bioengineering, 2025)
Medical physics is a field in which theories, concepts, and methodologies are employed to foster practical applications and technologies related to medical treatments. It should come as no surprise that cutting-edge developments in mathematical research are significantly contributing vital results to medical physics patients. In fact, many real-world medical physics scenarios can be attributed to the theoretical arrangements of intricate mathematical models themselves. Owing much of its inspiration to various physiological and biological systems, medical physics began to distinguish itself as an arena where the unification of mathematical constructs could have a considerable practical impact on human health. In a similar vein, new methodologies of quantum computing, of which many fundamental notions are wreathed with mystical intrigue, have lately surfaced in the mainstream news, garnering the attention of many contemporary mathematicians and medical physicists. Consequently, the aim of the present survey is to provide a precise computational framework intended for the mathematical medical physics community, and these investigations will be focused in particular on advancements towards radiation therapy treatment planning and its subsequent implementations. By incorporating the mathematical equations characterizing the physical phenomena of photon attenuation inside a biological organism, the problem of locating optimized radiation beam directions and intensities is translated into a combinatorial optimization problem. To address these optimization tasks, the intention is to develop a hybrid utilization of simulated annealing and other combinatorial optimization methodologies using a specific quantum computing framework. This new application field of quantum computing is showing promising results in providing feasible treatment blueprints generated by rapidly minimizing the integral dose delivered to the organs of interest within a configurable allowable dose constraint while maximizing the dose absorbed by the malignant region. As such, the hope is that this framework might embolden further research into the realm of quantum computing therapies in medical physics combatting the many challenges faced by traditional methodologies.